Proceedings of the First International Conference on Human Language Technology Research - HLT '01 2001
DOI: 10.3115/1072133.1072146
|View full text |Cite
|
Sign up to set email alerts
|

Conversational sales assistant for online shopping

Abstract: Websites of businesses should accommodate both customer needs and business requirements. Traditional menu-driven navigation and key word search do not allow users to describe their intentions precisely. We have developed a conversational interface to online shopping that provides convenient, personalized access to information using natural language dialog. User studies show significantly reduced length of interactions in terms of time and number of clicks in finding products. The core dialog engine is easily a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Figure 2 shows the start of a dialog. 2 1 See [1] for a survey of natural language interfaces to databases. 2 We are demonstrating the system at HLT'2001 [2].…”
Section: Natural Language Assistantmentioning
confidence: 99%
“…Figure 2 shows the start of a dialog. 2 1 See [1] for a survey of natural language interfaces to databases. 2 We are demonstrating the system at HLT'2001 [2].…”
Section: Natural Language Assistantmentioning
confidence: 99%
“…Ciechanowski et al (2018) emphasized the attention to the factors that cause trust or resistance to technology innovations between human as the user of information technology in the professional environment by comparing how people interact with various chatbots that mimic human ways of interaction as well as human expertise (Ciechanowski et al, 2018). Budzikowska et al (2001) found that a chatbot called 'Happy Assistant' in charge of helping users access e-commerce sites could find relevant information about products and services. They suggested that e-commerce sites with chatbot offer powerful personalized alternatives to traditional menu-driven or search-based interfaces to websites (Budzikowska et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Budzikowska et al (2001) found that a chatbot called 'Happy Assistant' in charge of helping users access e-commerce sites could find relevant information about products and services. They suggested that e-commerce sites with chatbot offer powerful personalized alternatives to traditional menu-driven or search-based interfaces to websites (Budzikowska et al, 2001). Other findings about the technological developments of chatbot have touched every aspect of human life that quantitative research analyzing factors influence technology acceptance of chatbot.…”
Section: Introductionmentioning
confidence: 99%
“…A second category proposes applications built for specific tasks [2], [3]. These systems are very effective in the domain for which they have been designed.…”
Section: Introductionmentioning
confidence: 99%